2020
DOI: 10.1109/access.2020.2966909
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Energy Savings and Operation of Active Distribution Networks Utilizing Hybrid Energy Resources and Soft Open Points: Case Study in Sohag, Egypt

Abstract: This research develops an overall framework for optimal operation of Hybrid Renewable Energy Resources (HRERs) system that involves the combination of PV/WT/Diesel units. In the proposed framework, a co-simulator tool is proposed to find the optimal scheduling of HRERs parameters. It composes HOMER PRO and NEPALN packages that are managed by C++ based online optimizer. Different scenarios of hybridization of energy resources are considered achieving technical, economic and environmental perspectives using the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 21 publications
0
13
0
1
Order By: Relevance
“…where n: the lifetime of the proposed hybrid system (years) which is assumed to be 20 years. COE is the average cost of electrical energy unit (kWh) which can be expressed as the follows [14,[22][23][24][25][26]:…”
Section: Evaluation Criteriamentioning
confidence: 99%
“…where n: the lifetime of the proposed hybrid system (years) which is assumed to be 20 years. COE is the average cost of electrical energy unit (kWh) which can be expressed as the follows [14,[22][23][24][25][26]:…”
Section: Evaluation Criteriamentioning
confidence: 99%
“…A new methodology is developed to identify the different configuration problems and maximize the techno-economic benefits of distribution systems for all envisaged cases and scenarios [12]. As well, other studies have identified the most convenient HRES option for the Public Library building, the hotel building, and other locations by evaluating the potential for energy sources in the proposed area using HOMER and a similar assessment tool [13][14][15][16][17][18]. When hybridizing energy sources, over one energy source in the system makes performance evaluation and decision-making complex and requires thorough technical, economic, and environmental analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Photovoltaic (PV) accounts for 55%, wind 28% and hydro-electric 11% of the renewable power generating capacity worldwide (Murdock, 2019). The International Renewable Energy Agency (IRENA) predicts that the global RES share will reach 85% of the total energy supply by 2050 (Shafik et al, 2020). However, both photovoltaic arrays and wind turbines are affected by environmental factors such as temperature and weather, so distributed energy generation (DEG) mode is mostly used.…”
Section: Introductionmentioning
confidence: 99%
“…An AC/DCNG was established in Universidad del Valle as part of MG (Franco-Mejia et al, 2017). And an ETAP model is established to compare with the field operation (Shafik et al, 2020).…”
Section: Introductionmentioning
confidence: 99%